Pendampingan Testing Aplikasi Pembelajaran Terintegrasi Artificial Intelligence untuk Meningkatkan Keterlibatan Siswa di Kabupaten Tangerang - Prihastomo, Yoga; Winanti, Winanti; Prabowo, Yulius Denny; Sidik, Achmad; Hendriyati, Penny; Luthfian, Muhamad; Setiawan, Rizky; Wardiansyah, Wardiansyah; Isbah, Latif Palikal; Chandra, Zaki Ma'rufan (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2025)
Problems faced by students in learning include boredom and monotony with conventional learning methods. Some schools have not yet utilized AI technology due to several factors, including the lack of a stable internet connection, teachers' concerns about AI technology causing student dependency, and low literacy regarding AI technology. The purpose of testing this AI-integrated learning application was to ensure that the application could be used by users without any problems. The method used in this activity was a hands-on practice using the Insan AI application by teachers and students. The results of the practice identified several things that needed to be improved, both technically, in terms of feature suitability and application reliability. This activity is expected to help the development team in ensuring that the application has no significant problems and is ready for use by users. It is hoped that this activity will soon be available for use by teachers and students in Tangerang Regency